Educação escolar para a cidadania - Arruda, Marcelo Della Justina (2007)
We know that education is one of the fundamental steps in the intellectual developing of the people, valorizing the human being in conscious and active citizens in the society, and this is what was analyzed and questioned in this dissertation as well as understanding that is the role of education to allow people with a real participation as citizenship. The question of the education is far more comprehensive than it can be thought. At school there are many difficulties related to the education, the students lack of interest is one of the main difficulties. The teachers have a very difficult mission such as develop the students interest, arousing in the students the wish of knowledge and change. To build up the citizenship we need to know clearly the goals of the education, allowing the students a bigger development and understanding about what a citizen is, where the citizen himself may free of the chains of alienation and realize that education is the main tool to the construction of a citizenship, where everybody has the right to life, health, education, leisure and freedom, and finally, to the dignity as human being. The methodology used to develop this paper is bibliographic research. This paper is developed in three chapters; the first is about school education, problems and difficulties in education and the school as an institution; the second chapter tries to give a concept of citizenship, and how it is possible to build it up; the third chapter discusses the relation of education and citizenship and how this relation can contribute in the construction of citizenship.